Neurons that Control Social States in Drosophila melanogaster - Jung, Yonil (California Institute of Technology, 2020)
Animal behaviors are influences not only by the immediate stimuli they are receiving but also by internal states. Internal states such as fear, hunger, and arousal can change subjective "feeling", and result in complex behavioral outcome even if animals receive the same stimuli. In most cases, these state-dependent behavioral changes persist long after the sensory input that caused internal state change is removed, and affect future behavior, reflexing previous experience. This feature of state-control allows animals to adapt their behavior to be more suitable for their internal demands.

The influence of the internal state on animal behavior has been emphasized for decades. There are multiple studies and attempts to identify persistent neuronal mechanisms which are the important feature of the internal state. However, how persistency makes the behavioral state interact with behavioral process to induce input/output relationship has been largely unknown. In addition, it is not clear what the behavioral functions of the persistence are, and what the circuit implementation of persistent activity is. Are there neurons that are persistently activated by external stimulus? Here we approached these questions by investigating social state of fruit flies, Drosophila melanogaster.

Fruit flies exhibit complex social behaviors that are appropriate for given social cues. For example, male flies show courtship behavior toward female flies, and show aggressive behavior such as wing threat and fighting when they encounter opponent male files. Previous studies have been focused on what sensory cues induce these behaviors: detection of female specific pheromones, 7,11-HD, causes male files to court, and male specific pheromone, cVA, induces inter-male aggression. In this study, we have focused more on how these cues might affect internal state changes rather than immediate behavioral response.

Studying persistent social state change has been challenging due to the difficulty of precise, time-resolved presentation of the social cues. For instance, courtship behaviors require constant presence of female object toward which male flies show oriented behavior. The male-male aggressive behaviors such as lunging and tussling require constant interaction between two animals, and removal of opponent male fly is technically impossible. Therefore, we first developed an optogenetic tool in fly systems to study persistent feature of the social state change to mimic transient presentation of the social cue. In Chapter II, we describe an optogenetic tool that allows the manipulation of neural activity in a freely moving fly. We used Red activatable Channelrhodopsin (ReachR), which enabled us to manipulate activation of neurons in freely behaving adult flies in millisecond precision without interfering normal visual function. Using such an activation tool, we show that activation of female sensing neurons, P1 neurons, induces persistent courtship behaviors in male flies that last several minutes after the stimulation of P1 neurons.

Although we show that persistent internal state change can be induced by transient stimulation of the sensory cues in Chapter II, the circuit implementation of such a persistency is not clear. In Chapter III, we show that activation of P1 neurons triggers persistent activity in its downstream neurons, pCd neurons, that is necessary for the persistent social behavior induced by transient social behaviors. Interestingly, manipulation of the pCd neurons do not affect immediate behavioral response that are shown during the presentation of social cues (P1 stimulation), implying that there are parallel and dissociable pathways for the immediate response and enduring response derived from persistent internal state change, although these responses are caused by common cue. Although the neural mechanism to encode persistent activity is still unclear, this finding shows how internal state and command pathway interact with each other to affect behavioral outcome.

Altogether, these findings described in this dissertation offer new insights for future researchers to understand behavioral state control.
Keywords: Behavioral Neuroscience; Biochemistry and Molecular Biophysics; Drosophila Melanogaster; Social Behavior